PENGARUH LINGKUNGAN KERJA DAN STRES KERJA SERTA MOTIVASI TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN PENELITIAN DAN PENGEMBANGAN KABUPATEN KARANGASEM - I Ketut Mustika (Journal of Applied Management Studies, 2022)
This study aims to analyze the effect of the work environment and work stress and motivation on employee performance at the Regional Research and Development Planning Agency of Karangasem Regency. The sample analysis technique uses the saturated sample method where the sample is all employees of the Regional Research and Development Planning Agency of Karangasem Regency, totaling 69 people. The analytical technique used is using multiple linear regression analysis with the help of SPSS version 25. The results of the analysis show that 1) the work environment has a positive and significant effect on employee performance; 2) work stress has a positive and significant effect on employee performance; 3) motivation has a positive and significant effect on employee performance; and 4) work environment and work stress as well as motivation have a positive and significant effect simultaneously on employee performance. Suggestions in this study is that the management pays more attention to the employee's work environment and improves the management of work stress and motivation to employees to improve employee performance in achieving organizational goals.